2015
DOI: 10.1038/ijo.2015.226
|View full text |Cite
|
Sign up to set email alerts
|

Surgical removal of inflamed epididymal white adipose tissue attenuates the development of non-alcoholic steatohepatitis in obesity

Abstract: Background:Non-alcoholic fatty liver disease (NAFLD) is strongly associated with abdominal obesity. Growing evidence suggests that inflammation in specific depots of white adipose tissue (WAT) has a key role in NAFLD progression, but experimental evidence for a causal role of WAT is lacking.Methods:A time-course study in C57BL/6J mice was performed to establish which WAT depot is most susceptible to develop inflammation during high-fat diet (HFD)-induced obesity. Crown-like structures (CLS) were quantified in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
102
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(113 citation statements)
references
References 38 publications
10
102
1
Order By: Relevance
“…In comparison with other strains, C57BL/6J are obesityprone mice and their eWAT is a higher HFD-susceptible fat depot, whose mass increases more than mesenteric or inguinal WAT depots [34]. However, besides epididymal, other fat depots such as mesenteric, inguinal/subcutaneous and perirenal fat depots can also account for the increase of body weight in UN/HFD mice.…”
Section: Discussionmentioning
confidence: 97%
“…In comparison with other strains, C57BL/6J are obesityprone mice and their eWAT is a higher HFD-susceptible fat depot, whose mass increases more than mesenteric or inguinal WAT depots [34]. However, besides epididymal, other fat depots such as mesenteric, inguinal/subcutaneous and perirenal fat depots can also account for the increase of body weight in UN/HFD mice.…”
Section: Discussionmentioning
confidence: 97%
“…Notably, these fatty acids are also increased in patients with diagnosed NASH41. Furthermore, surgical excision of inflamed WAT in mice lowered palmitic acid in plasma and reduced progression towards NASH5. In vitro experiments have shown that conditioned medium from palmitic acid-treated hepatocytes induces the expression of pro-fibrotic genes in hepatic stellate cells42, providing mechanistic support for a crucial role of inflammatory lipid mediators in NASH.…”
Section: Discussionmentioning
confidence: 99%
“…Liver and epididymal white adipose tissue (eWAT) was weighed at the closure of the high-fat diet experiments and stored for further analyses at –80°C. We analysed eWAT as it can be reliably identified and weighed and because inflamed eWAT consequent to a high-fat diet has been implicated in the pathogenesis of non-alcoholic fatty liver disease 23 24…”
Section: Methodsmentioning
confidence: 99%